Antiviral effect and mechanism of Phillyrin and its reformulated FS21 against influenza. Issue 3 (1st March 2023) - Chen, Yan; Wu, Cunjin; Li, Huifen; Powell, Harrison; Chen, Allison; Zhu, Guodong; Cong, Weihong; Fu, Li; Pekosz, Andrew; Leng, Sean X.
Abstract: Background: Influenza virus causes significant morbidity and mortality with pandemic threat. Oleaceae Fructus Forsythiae is a medicinal herb. This study aimed to investigate antiviral effect of Phillyrin, a purified bioactive compound from this herb, and its reformulated preparation FS21 against influenza and its mechanism. Methods: Madin–Darby Canine Kidney (MDCK) cells were infected by one of six influenza viruses: five influenza A viruses (IAVs: three H1N1 and two H3N2) and one influenza B virus (IBV). Virus‐induced cytopathic effects were observed and recorded under microscope. Viral replication and mRNA transcription were evaluated by quantitative polymerase chain reaction (qPCR) and protein expression by Western blot. Infectious virus production was assessed using TCID50 assay, and IC50 was calculated accordingly. Pretreatment and time‐of‐addition experiments with Phillyrin or FS21 added 1 h before or in early (0–3 h), mid (3–6 h), or late (6–9 h) stages of viral infection were performed to assess their antiviral effects. Mechanistic studies included hemagglutination and neuraminidase inhibition, viral binding and entry, endosomal acidification, and plasmid‐based influenza RNA polymerase activity. Results: Phillyrin and FS21 had potent antiviral effects against all six IAV and IBV in a dose‐dependent manner. Mechanistic studies showed that both suppressed influenza viral RNA polymerase with no effect on virus‐mediated hemagglutination inhibition, viral binding or entry, endosomal acidification, or neuraminidase activity. Conclusions: Phillyrin and FS21 have broad and potent antiviral effects against influenza viruses with inhibition of viral RNA polymerase as the distinct antiviral mechanism.